Effect of fertigation schedule on production potential, quality and nutrient uptake of elephant-foot yam (Amorphophallus paeoniifolius) (Current Horticulture, 2024)
The field experiment was conducted to determine the effect of fertigation schedule on productivity and quality of elephant-foot yam (Amorphophallus paeoniifolius Dennst. Nicolson) at Bhubaneswar Regional Centre of CTCRI, Thiauvananthapuram, during 2013 and 2014. The experiment was laid out in split plot design with different fertigation intervals (T1:2, T2:3 and T3:4 days intervals) in the main plots. The recommended dose of fertilizers (soluble fertilizer N, P2O5, K2O @ 120-60-120 kg/ha) were applied in splits (S1:30, S2:40 and S3:50) through drip irrigation in sub-plots. A check [surface irrigation with P2O5 60 kg/ha as basal and N, K2O @ 120-120 kg/ha during first (40%), second (30%) and third (30%) month after planting (MAP) applied to soil] and the control (surface irrigation without fertilizer) treatments were also included. All the treatments had three replications. The plant height, canopy spread and pseudostem (leaf petiole) girth at third and fifth MAP were maximum in treatments which received maximum nutrients. The treatments T3S2 (fertigation in 40 split doses at 4 days interval) and T2S3 (fertigation in 50 split doses at 3 days interval) resulted in more corm yield, dry matter and starch content, nutrient (N, P and K) uptake and use efficiency (agronomic efficiency, recovery efficiency and partial factor productivity) but difference between the two treatments were not statistically significant. The control (surface irrigation without fertilizer) resulted in lower calcium oxalate content in corm. Dilution effect of calcium oxalate content was recorded in treatments that resulted in maximum corm yield.
Keywords: Elephant-foot yam; Fertigation; Nutrient uptake; Quality; Yield; Canopy; Pseudostem; Dry matter